ASPEK HISTORI DAN PERKEMBANGAN UNDANG-UNDANG TENTANG PENCEGAHAN DAN PEMBERANTASAN TINDAK PIDANA PENCUCIAN UANG - Simanjuntak, Richan (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
Since 1930, money laundering has become an international concern and a crime with international dimensions. Perpetrators of "white-collar" crimes with a high social, educational, and financial background are involved in this practice. Adequate law enforcement efforts and regulations are needed to combat this practice. In Indonesia, money laundering laws have been amended and updated in an effort to prevent and eradicate this practice. This research uses a normative legal research method that focuses on legal norms related to the Prevention and Eradication of Money Laundering Crimes. Primary data is obtained from secondary sources such as existing laws, while primary data serves as supporting information. The data collection method used is literature review. Data is analyzed descriptively qualitatively, and conclusions are drawn using deductive thinking methods. In the context of preventing and eradicating Money Laundering Crimes, this law not only regulates what criminal acts constitute money laundering but also establishes an institution called the Financial Transaction Reports and Analysis Center (PPATK). Based on Law Number 15 of 2002, Money Laundering is considered a white-collar crime. Indonesia has Law Number 8 of 2010 on the Prevention and Eradication of Money Laundering, which was created based on Indonesia's participation in The Asia/Pacific Group on Money Laundering. Changes were made from Law Number 25 of 2003 to Law Number 8 of 2010, including provisions regarding financial supervision and cooperation in the prevention and eradication of money laundering crimes.